An Efficient Stereoselective Total Synthesis of All Stereoisomers of the Antibiotic Thiamphenicol through Ruthenium‐Catalyzed Asymmetric Reduction by Dynamic Kinetic Resolution (Eur. J. Org. Chem. 27/2015). Issue 27 (September 2015) - Perez, Marc; Echeverria, Pierre‐Georges; Martinez‐Arripe, Elsa; Ez Zoubir, Mehdi; Touati, Ridha; Zhang, Zhaoguo; Genet, Jean‐Pierre; Phansavath, Phannarath; Ayad, Tahar; Ratovelomanana‐Vidal, Virginie
Abstract : The cover picture shows how chemists, by the judicious choice of the catalytic system, can control the stereochemical outcome of the ruthenium‐catalyzed enantioselective reduction of an inexpensive and readily available racemic α‐amido‐β‐keto ester derivative. More particularly, a dynamic kinetic resolution (DKR) process, through either asymmetric hydrogenation (AH) or asymmetric transfer hydrogenation (ATH), allowed the formation of the essential syn oranti relationship of key amino alcohols leading to the synthesis of all four stereoisomers of the antibiotic thiamphenicol. Details are discussed in the article by T. Ayad, V. Ratovelomanana‐Vidal et al. on5949 ff .